STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI ANAK BERKEBUTUHAN KHUSUS (ABK) TUNARUNGU DI SLB/ B KARYA BAKTI DON BOSCO WONOSOBO - Azima Prisma Vera; Sri Haryanto; Ahmad Khoiri (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2022)
The background of this study is about almost 80% of male Muslim students in the Catholic Foundation of the Deaf Children Education Institute Special Education School Karya Bakti Don Bosco in studying Islamic Religious Education at school. The purpose of this study is to determine the process of implementing islamic education learning, the obstacles experienced by teachers in the learning process and teachers' efforts in dealing with learning obstacles. The results showed that the process of implementing islamic eduvation learning for deaf students at Special Educatin School Karya Bakti Don Bosco was carried out in the afternoon on a scheduled basis using references adopted from lesson plan for normal children, the learning methods used were classical lecture methods, and evaluation assessments using formative and summative methods. The obstacles faced by teachers are communication obstacles, emotional obstacles, and the duration of understanding student material, Efforts made by teachers in dealing with obstacles are by applying teaching and learning methods, face to face methods, varied learning methods adjusted to the abilities of students and rote memorization methods.